Pengembangan Aplikasi Tracer Study untuk Mengetahui Keterserapan dan Kepuasan Pengguna Alumni Teknologi Pendidikan FIP UNM - Lonang, Anisa Hardiyani; Abdul Hakim; Farida Febriati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The aim of this development research is to identify the needs for a Tracer Study application that covers alumni absorption and user satisfaction in the Educational Technology Department of FIP UNM, to design the Tracer Study application, and to measure the level of validity and practicality of the application from the alumni's perspective. The research method used is a Research and Development (R&D) approach with the Alessi & Trollip development model, which consists of three main stages: planning, design, and development. Data collection techniques included observation and questionnaires. This research was conducted in the Faculty of Education, Department of Educational Technology, with 25 alumni and 2 lecturers as research subjects. The results show that alumni have a high need for a Tracer Study application as a medium for tracking graduates. The application was designed using the Kodular platform, featuring a homepage with a welcome message, user guide, and login access. The application consists of six main pages, including a dashboard, alumni data, and a profile questionnaire. The validity test was carried out in two stages: an alpha test by a media design expert which resulted in a “very good” qualification, and a content expert assessment which resulted in a “good” qualification. A beta test was conducted through trials with a small group of alumni selected through random sampling, resulting in a “good” qualification. Trials with a larger group also showed a “good” qualification. In conclusion, the developed Tracer Study application is proven to be valid and practical for use by alumni of the Educational Technology Department at FIP UNM as a tool for tracking graduate data and evaluating academic programs. Keywords: educational technologi alumni, development, tracer study